2018
DOI: 10.1016/j.msec.2018.04.028
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the androstane lung cancer inhibitor content on the cell-selective toxicity of hydroxyapatite-chitosan-PLGA nanocomposites

Abstract: An androstane (17β-hydroxy-17α-picolyl-androst-5-en-3β-yl-acetate (derivative A)) cancer inhibitor was successfully captured in a carrier made of nano-sized hydroxyapatite (HAp) coated with chitosan-PLGA polymer blends (Ch-PLGA). In our previous studies, we demonstrated that it was convenient to use spherical HAp/Ch-PLGA carriers as vehicles to target the lungs following intravenous administration. In this study, we used emulsification and subsequent freeze-drying to load the spherical HAp/Ch-PLGA carriers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…All bands are also found in the chitosan spectra reported by others. 19,28 The appearance of bands characteristic for pure Biginelli derivatives A, B and C in the spectra of the A-Ch and B-Ch and C-Ch systems may be indicative of Biginelli pyrimidines entrapped in Ch during the synthesis of NPs. Furthermore, an increased intensity of the C-H band near 3200 cm À1 in the spectra of the A-Ch, B-Ch and C-Ch systems as compared to the spectra of pure A, B and C, respectively, is probably due to hydrogen bonding between A, B and C Biginelli derivatives and Ch.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All bands are also found in the chitosan spectra reported by others. 19,28 The appearance of bands characteristic for pure Biginelli derivatives A, B and C in the spectra of the A-Ch and B-Ch and C-Ch systems may be indicative of Biginelli pyrimidines entrapped in Ch during the synthesis of NPs. Furthermore, an increased intensity of the C-H band near 3200 cm À1 in the spectra of the A-Ch, B-Ch and C-Ch systems as compared to the spectra of pure A, B and C, respectively, is probably due to hydrogen bonding between A, B and C Biginelli derivatives and Ch.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous examples demonstrating how different technological operations can change the effects of active pharmaceutical ingredients in appropriate drugs. [18][19][20] In Fig. 4 SEM micrographs of (a) A-Ch, (b) B-Ch, and (c) C-Ch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyapatite is an inorganic bone component widely used in bone tissue reconstruction, and more recent studies have found that hydroxyapatite nanoparticles have selective anticancer activity for lung cancer cells. Ignjatovic et al (38) demonstrate that it is possible to develop hydroxyapatite nanoparticle with chitosan and poly-lactic-co-glycolic (PLGA) to make them more selective for the A549 lung cancer cell line than for healthy cells. Chen et al (39) also makes use of nanoparticles of hydroxyapatite in the delivery of ionizing radiation for the treatment of lung cancer, obtaining positive results and proposing a new alternative for the treatment of lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…%) were designed and their potential for activity toward lung cancer cells examined. 21 As the content of derivative A increased, so did the median value of the particle size distribution, with the particles containing 7.5, 11.2 and 15 wt.% A having the d 50 values of 167, 168 and 231 nm, respectively. The cancer cell targeting potential of the particles was examined simultaneously on human lung cancer cells (A549) and human lung fibroblasts (MRC5) using the dye exclusion assay (DET) and the colorimetric test with the tetrazolium salt (MTT).…”
Section: Nano-bio Materials For Preventive and Regenerative Medicinementioning
confidence: 98%